Beyond the Protected World Heritage in Brazil - E. Fonseca Filho, Ricardo; Amália de Oliveira, Maria; de S. Braga, Solano; Duarte Pimentel, Thiago (Anais Brasileiros de Estudos Turísticos, 2022)
Heritage is at risk for several reasons: economic, health, climate, political, social and war crises. Even with the auspices of Unesco, the title of World Heritage, by itself, does not always protect the sites that have received this seal of approval. Brazil, with 23 World Heritage sites, whether cultural, natural and/or mixed, reflects in its territory aspects of this crisis that, in part, is the result of a disordered tourism. The dossier Tourism and Unesco World Heritage Sites in Brazil, from the Anais Brasileiros de Estudos Turísticos (Brazilian Annals of Tourism Studies), showed, through seven articles, several aspects and approaches about tourism in sites that house the national heritage recognized by Unesco. It was observed in the dossier that, in addition to the world heritage title, effective public policies and territorial management with popular participation are needed so that the "heritage-territory" is not reproduced, which touristifies in an unsustainable way. It is hoped that the heritage will primarily serve the communities inserted in and around these sites. And that even in areas already gentrified, governments, educational institutions and private companies may act to reinsert and integrate local communities and traditional populations in the tourist activity and as agents of heritage protection.